Left atrial appendage occlusion in high-risk patients with non-valvular atrial fibrillation. Issue 24 (4th August 2016) - Berti, Sergio; Pastormerlo, Luigi Emilio; Rezzaghi, Marco; Trianni, Giuseppe; Paradossi, Umberto; Cerone, Elisa; Ravani, Marcello; De Caterina, Alberto Ranieri; Rizza, Antonio; Palmieri, Cataldo
Abstract : Objective: Percutaneous left atrial appendage (LAA) occlusion has been developed as a viable option for stroke and thromboembolism prevention in patients with non-valvular atrial fibrillation (NVAF) and at high risk for cerebral cardioembolic events. Data on device implantation and long-term follow-up from large cohorts are limited. Methods: 110 consecutive patients with NVAF and contraindications to oral anticoagulants (OACs) underwent LAA occlusion procedures and achieved a longer than 1 year follow-up. All patients were enrolled in a prospective registry. Procedures were performed using the Amplatzer Cardiac Plug or Amulet guided by fluoroscopy and intracardiac echocardiography. Results: Mean age of the population was 77±6 years old; 68 were men. Atrial fibrillation was paroxysmal in 20%, persistent in 15.5% and permanent in 64.5% of cases, respectively. Mean CHA2 DS2 -VASc and HAS-BLED scores were 4.3±1.3 and 3.4±1, respectively. Technical success (successful deployment and implantation of device) was achieved in 100% of procedures. Procedural success (technical success without major procedure-related complications) was achieved in 96.4%, with a 3.6% rate of major procedural complications (three cases of pericardial tamponade requiring drainage and one case of major bleeding). Mean follow-up was 30±12 months (264 patient-years). Annual rates for ischaemic stroke and for other thromboembolic events were respectively 2.2% and 0%, and annual rate for major bleeding was 1.1%. Conclusions: Our data suggest LAA occlusion in high-risk patients with NVAF not suitable for OACs is feasible and associated with low complication rates as well as low rates of stroke and major bleeding at long-term follow-up.